Avaliação das alterações morfológicas do forame apical após ampliação foraminal: uma revisão sistemática - Isabella Figueiredo Assis Macedo (2022)
This systematic review aimed to evaluate the morphological alterations of the apical foramen after foraminal enlargement procedure. Electronic searches were performed in PubMed/Medline, Scopus, Web of Science, SciELO, Embase, Google Scholar databases and reference lists until April 2022. Only ex vivo studies evaluating the influence of foraminal enlargement on morphological changes of the apical foramen were included. Studies without a control group or full text available were excluded. Foraminal deformation and increased area were considered the primary outcomes. The risk of bias assessment was performed according to a modified Joanna Briggs Institute checklist. Seven hundred two studies were retrieved, of which thirteen were eligible for qualitative analysis. Most studies used maxillary or mandibular molars with curved root canals and rotary and reciprocating systems for instrumentation. The working length determined by the included studies ranged from two millimeters short to one millimeter beyond the apical foramen. Regarding foraminal deformation, of the studies included in this review, eight found an increase in foramen deformation after foraminal enlargement, while five did not observe a significant influence. Among eight studies that evaluated the foraminal area, all found an increase in the area after foraminal enlargement. Insufficient data for touched/untouched cemental walls by endodontic instruments and formation of dentin microcracks were observed. A low risk was found in the risk of bias analysis of eligible studies. Within the limitations of this review, it is noted that foraminal enlargement during root canal preparation seems to increase the deformation and area of the apical foramen, especially when the working length exceeds the limit of the greater foramen by at least one millimeter. However, it was not possible to conclude whether there is a conservative but effective protocol for foraminal enlargement due to the great methodological heterogeneity of the studies. Future investigations with standardized methodologies are encouraged in order to provide more robust evidence.